Perancangan SIMAK TK Sultan Agung UII - Wardana, Dimas Zaeca; Arifin, Aridhanyati (JATISI, 2025)
Recording and managing academic data of Sultan Agung UII Kindergarten is still done simply using Ms Word and Ms Excel. Recording and managing data like this has the disadvantage of being inefficient and prone to duplication of data so that the information presented is likely to be inaccurate. In addition, school promotion using IG social media is not effective enough to convey the school's profile and credibility. Therefore, it is necessary to support the school website for the advancement of students and the school. System development uses the Waterfall method, PHP programming language, MySQL database, and Laravel framework. Data collection is done through interviews and observations. The testing method uses black box testing and usability testing. The results of this system design are use case diagram, activity diagram, and database design. The website results in the form of a school profile and SIMAK. Based on the results of Black Box testing, it is known that all features can run well. Based on the results of Usability testing obtained a score of 86.25 in grade (value) A and get a very good rating (Excellent).